Deposition and characterisation of a porous Sn(IV) semiconductor nanofilm on boron-doped diamond - Hyde, M; Saterlay, A; Wilkins, S; Foord, J; Compton, R; Marken, F (2002)
Nanofilm deposits of a porous Sn(IV) oxide are formed by anodic electrodeposition on a polished boron-doped diamond electrode immersed in an aqueous Sn2+ solution. Mechanically and electrochemically stable deposits of 10-15 nm thickness are formed irrespective of the Sn2+ concentration and mass-transport enhancement by power ultrasound. Atomic force microscopy images indicate the presence of a smooth and noncrystalline film, which is stable under ambient conditions. n-type semiconducting characteristics are observed for the aqueous solution redox couples Fe(CN)63-/4- and Ru(NH3)63+/2+. However, preliminary results from voltammetric experiments indicate that the small and neutral organic molecule N,N,N′,N′-tetramethylphenylenediamine is able to diffuse through the porous film to undergo oxidation directly at the surface of the boron-doped diamond electrode.